The synthesis and biological evaluation of a novel class of butyrylcholinesterase inhibitors using isosorbide as a building block - Dillon, Gerald (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2007)
The aim of this project was to synthesise and optimise a novel class of cholinesterase inhibitors using the simple sugar, isosorbide, as a building block and to assess the inhibitory activity of these compounds in vitro. Cholinesterases are enzymes that can hydrolyse choline esters into their respective acid and choline portions. There are two types of cholinesterases, namely, acetylcholinesterase (AChE) [E.C. 3.1.1.7] and butyrylcholinesterase (BuChE) [B.C. 3.1.1.8]. While it is known that AChE has a specific biological role in the body, the biological function of BuChE is, as yet, unclear. In the last number of years, several lines of medical research have independently reported upon a link associating BuChE with the onset of Alzheimer’s disease (AD). Inhibitors of this enzyme are therefore highly desirable for the elucidation of the biological role of BuChE but also, as potential therapeutics for the treatment of AD. The design of huBuChE (human butyrylcholinesterase) inhibitors was based on the discovery that 2-ester derivatives of isosorbide are hydrolysed by BuChE with exceptional rapidity, demonstrating a high level of affinity and molecular recognition of these compounds for BuChE. It was therefore proposed that highly potent and selective inhibitors of BuChE could be synthesised by replacing the vulnerable 2-ester group with a carbamate group, which is understood to be capable of interacting with BuChE and causing the inhibition of the enzyme. Two initial families of compounds were synthesised, referred to as group 1 and group 2 compounds, which possessed either a carbamate or 'reversed carbamate' group at position-2 of isosorbide. Chapter 2 focuses on the development of group 2 'reversed carbamate' compounds. This chapter describes the synthesis and evaluation of 17 test compounds, which were completely novel in structure and which transpired, in some cases, to be moderate inhibitors of huBuChE, with the lead compound 106 having an IC50 of 1.5 [iM for huBuChE. Chapter 3 focuses on the synthesis and evaluation of group 1 carbamates, with particular emphasis in optimising the type of substitution at position-5 of isosorbide, as it was found that a benzyl carbamate was the optimum group for inhibition in position-2. The work in this chapter produced a total of 29 test compounds, which includes a range of highly potent and selective inhibitors of huBuChE with the lead compounds 121 and 124 having IC50 values for huBuChE of 5.77 and 12.33 nM respectively.
Keywords: Pharmacology, Ph.D.; Ph.D. Trinity College Dublin